Women with disabilities: the long road to equality. - Fairchild SR (Journal of Human Behavior in the Social Environment, 2002)
Although the passage of the Americans with Disabilities Act (ADA) was instrumental in raising societal conscious awareness of the issues and discriminatory practices towards people with disabilities, the evidence points to a lack of full inclusion in the mainstream of American society. Due to the double discrimination of gender and disability status, women with disabilities confront major obstacles even more boldly to achieve equality and full participation in society. This article examines some of the current meanings of disability, vital statistics, and current discriminatory practices in specific areas for women with disabilities such as, human rights and abuse, relationships and sexual functioning, health maintenance issues, employment, and environmental barriers. Positive strategies for social workers to become involved at both the macro and micro levels of practice as well as social policy level are identified.